"Direct vision" operation of posterior atlantoaxial transpedicular screw fixation for unstable atlantoaxial fractures: A retrospective study. Issue 25 (June 2017) - Cao, Liangliang; Yang, Erzhu; Xu, Jianguang; Lian, Xiaofeng; Cai, Bin; Liu, Xiaokang; Zhang, Guowang
Abstract: Background: The posterior screw fixation in atlas via posterior arch and lateral mass, also called C1 "pedicle" screw, combined with C2 pedicle screw fixiation has shown better biomechanical stability in unstable atlantoaxial fractures. However, its popularization has to fulfill the limitation imposed by anatomical characteristics. The aim of this study was to explore the manipulation, effect, and safety of the atlantoaxial transpedicular screw fixation under "direct vision" for the treatment of unstable atlantoaxial fracture. Methods: All the patients diagnosed with unstable atlantoaxial fracture, who received surgery treatment of C1, C2 internal fixation from January 2012 to December 2014 were reviewed. Only these patients that were diagnosed with atlantoaxial unstability secondary to trauma and were treated with atlantoaxial transpedicular screw fixation under "direct vision" and iliac autograft were included. The safety of transpedicular screw placement, postoperative outcome, atlantoaxial stability, autograft fusion, and complications was observed and analyzed retrospectively. The pain visual analog scale (VAS) and the Japanese Orthopedic Association (JOA) score were used as surgical curative effect evaluation standards. Results: We reviewed a total of 92 patients diagnosed with unstable atlantoaxial fracture, who received surgery treatment of C1, C2 internal fixation from January 2012 to December 2014, and 87 patients were treated with atlantoaxial transpedicular screw fixation under "direct vision" and were included this analysis. A total of 306 transpedicular screws in atlas and axis were placed successfully. All cases were followed-up >12 months. The overall breach rate was 11.36%. None of the breaches resulted in new-onset neurological sequela. The neurological status in cases with bilateral upper extremities numbness and lower extremities weakness had improved after surgery. At the latest follow-up, the neck VAS and JOA scores were significantly improved ( P < .01) than those preoperatively. No cases demonstrated implantation failure and bone graft absorption on the postoperative x-ray films and CT scans. Conclusion: Atlantoaxial transpedicular screw fixation under "direct vision" and iliac autograft for the treatment of unstable atlantoaxial fracture has shown simple manipulation and efficient performance. Thus, the technique of C1–C2 fixation is feasible in treating unstable atlantoaxial fracture. Abstract : Supplemental Digital Content is available in the text